Debating the Options for Type 2 Diabetes Mellitus Prevention - Canavan, Neil (MD Conference Express, 2008)
This article not only discusses the best treatment option for diagnosed type 2 diabetes mellitus (T2DM), but also the most prudent ways to prevent the onset of diabetes including managing at-risk individuals who (at present) only show evidence of impaired glucose tolerance, insulin resistance, or beta-cell function — so-called “prediabetics.”